2009
DOI: 10.1002/psp.564
|View full text |Cite
|
Sign up to set email alerts
|

An application of spatially autoregressive models to the study of US county mortality rates

Abstract: County mortality rates in the US tend to be associated with social and economic resources of counties and the unequal distribution of these resources across space. The processes that generate these social and economic inequalities are often tied to geographical location. In this paper, we present an application of spatially autoregressive models of US county mortality rates that control for the social and economic conditions that often infl uence mortality rates and the effects of spatial structure of counties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 42 publications
4
31
0
1
Order By: Relevance
“…Social scientists have found significant between-place differences in many indicators of wellbeing in the U.S., including employment (Smith and Glauber 2013), income (Peters 2013), education (Roscigno, Tomaskovic-Devey, and Crowley 2006), poverty (Cotter, Hermsen, and Vanneman 2007; Curtis, Voss, and Long 2012), program participation (Slack and Myers 2014), health and mortality (Burton et al 2013; Sparks and Sparks 2010), and residential segregation (Downey 2003). Many of these studies examined outcomes at the county level, but others explored employment, wage, educational, and health disparities at other geographic scales (e.g., states, regions, and (non)metropolitan areas) (Lochner et al 2001; Smith and Glauber 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Social scientists have found significant between-place differences in many indicators of wellbeing in the U.S., including employment (Smith and Glauber 2013), income (Peters 2013), education (Roscigno, Tomaskovic-Devey, and Crowley 2006), poverty (Cotter, Hermsen, and Vanneman 2007; Curtis, Voss, and Long 2012), program participation (Slack and Myers 2014), health and mortality (Burton et al 2013; Sparks and Sparks 2010), and residential segregation (Downey 2003). Many of these studies examined outcomes at the county level, but others explored employment, wage, educational, and health disparities at other geographic scales (e.g., states, regions, and (non)metropolitan areas) (Lochner et al 2001; Smith and Glauber 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Fewer studies still consider the spatial structure underlying the data and spatial dependence which may bias statistical estimates and generate misleading conclusions (Cressie, 1993; Haining, 2003; Voss, Long, Hammer, & Friedman, 2006). Spatial analysis approaches that contend with spatial dependence have been uncommon in mortality research until recently (McLaughlin, Stokes, Smith, & Nonoyama, 2007; Sparks & Sparks, 2010; Yang, Jensen, & Haran, 2011; Yang, Teng, & Haran, 2009), and this work does not focus on income inequality.…”
Section: Introductionmentioning
confidence: 99%
“…One of the dominant spatial autoregressive regression models is the spatial lag model (Ward and Gleditsch 2008) where a spatial lagged effect of the dependent variable is included into the analysis. It has been argued that the spatial lag model could capture the spatial homogeneity embedded in spatial data and has been widely used in previous research (Sparks and Sparks 2010; Yang et al 2011; Sparks et al 2012). To the best of our knowledge, Páez et al (2002) first demonstrated that a spatial lag effect could be fused into a Gaussian-based GWR and be estimated with the maximum likelihood (ML) approach.…”
Section: Methodsmentioning
confidence: 99%